2010
DOI: 10.3141/2160-04
|View full text |Cite
|
Sign up to set email alerts
|

Development of Data Collection and Integration Framework for Road Inventory Data

Abstract: The availability and quality of transportation data is a cornerstone of any data-driven program. There is a continuous need to identify and develop alternative, reliable, and inexpensive sources of data and efficient and robust integration techniques. This research presents an innovative cost-effective application to collect geographic information system (GIS)–compatible data from image-based databases. Road inventory data on guardrail end-type locations along with other road features on more than 8,000 mi of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The data were collected on the Wisconsin state trunk network (STN) from the Wisconsin DOT Photolog data set, which has a scale of 0.01 mi (52.8 ft), by using an automated algorithm in a geographic information system (GIS) environment (24). The data were mapped with the Photolog lane mile routes, which were created to enable the integration of Photolog-based data with other Wisconsin DOT GIS databases (25).…”
Section: Horizontal Curve Datamentioning
confidence: 99%
“…The data were collected on the Wisconsin state trunk network (STN) from the Wisconsin DOT Photolog data set, which has a scale of 0.01 mi (52.8 ft), by using an automated algorithm in a geographic information system (GIS) environment (24). The data were mapped with the Photolog lane mile routes, which were created to enable the integration of Photolog-based data with other Wisconsin DOT GIS databases (25).…”
Section: Horizontal Curve Datamentioning
confidence: 99%
“…Therefore, de Frutos et al suggested to use smartphone-based cameras and apps for video inspections [19], an alternative option to the more expensive terrestrial laser scanning [20]. Besides, process chains to collect and evaluate image data using GIS-based handling of camera-based material and frames have been recommended [21]. The extraction of infrastructure data can be achieved using computer vision, which was already recommended for camera-based road inspections, but mainly applied for pavement analysis and road sign detection [22].…”
Section: State Of Art Of Gis-based Wvc Analysismentioning
confidence: 99%
“…The horizontal curve data included attribute information, such as radius, degree of curvature, length, route, county, and the mile marker for the start and end point of each curve. The data were mapped with the photo log lane mile routes, which were created to enable the integration of photo log-based data with other Wisconsin DOT geographic information system (GIS) databases (22). For data analysis, the horizontal curve location was selected as the spatial unit of analysis for which other data elements and attributes would be collected and assembled.…”
Section: Hallmark Et Al (14)mentioning
confidence: 99%
“…However, the data are not readily integrated with the Wisconsin DOT STN database. Therefore, the Sign View data were mapped with the photo log lane mile routes to enable integration with the other data set (22). For the purpose of this research, the focus was only on turn (W1-1) and curve (W1-2) signs to explore the relationship between the use of the two signs and safety at horizontal curves.…”
Section: Sign Datamentioning
confidence: 99%